FMD EPIDEMIC PROCESS CHARACTERISTICS IN RUSSIA IN 2010 – FIRST QUARTER OF 2019 - V. P. Semakina; T. P. Akimova; A. K. Karaulov (Ветеринария сегодня)
Foot-and-mouth disease is a highly contagious viral disease of cloven-hoofed livestock and wild animals. Europe, North America and Oceania have long been FMD free; at the same time, the virus is widely spread in Asian and African countries. In the period from 2010 to March 2019, FMD was notified to the World Organisation for Animal Health (OIE) by 89 countries of the world. Local FMD outbreaks were also reported in several regions of the Russian Federation throughout this period. The research was aimed at studying some characteristics of the FMD epidemic process in the Russian Federation. The undertaken epidemiological analysis covers the Russian Federation regions where FMD outbreaks were reported between 2010 and March 2019. During the period under consideration, FMD cases were reported in 9 regions of the Russian Federation, mainly in the settlements located in close proximity to the Russia-China and Russia-Mongolia international borders. Most of the outbreaks were caused by serotype O and A FMD viruses. In most cases, FMD was reported in cattle and pigs and, less frequently, in sheep and goats. The analysis of the FMD epidemic situation in the Russian Federation Subjects was performed through epidemic process assessment based on the following estimates: the proportion of infected settlements, epidemic, contagiousness and morbidity rates. The Zabaykalsky and Primorsky Krais have a lead in the number of infected settlements. The highest morbidity rate in pigs was recorded in the Primorsky Krai, in cattle – in the Amur Oblast. The epidemic rate was the highest in the Primorsky and Zabaykalsky Krais. The Primorsky Krai also accounted for the highest contagiousness rates in 2014 and 2019 when FMD occurred on several large pig farms.